2014
DOI: 10.3109/02713683.2014.884596
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Changes in Trabecular Meshwork after Patterned and Argon Laser Trabeculoplasty in Cats

Abstract: When used at sub-threshold power, PLT caused less thermal damage to the trabecular meshwork than ALT. However, it did not effectively prevent late scarring of the trabecular meshwork in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The impact of previous surgeries on GATT prognosis remains unclear [18][19][20][21]. In our cohort, eyes with prior ocular surgery history exhibited an inferior GATT success rate, likely attributed to scarring, in ammation, or brotic changes within the TM after previous trabeculectomy (5 eyes) or intraocular environmental disturbance caused by other ocular surgery (one eye with lens subluxation) [20,[22][23][24].…”
Section: Discussionmentioning
confidence: 94%
“…The impact of previous surgeries on GATT prognosis remains unclear [18][19][20][21]. In our cohort, eyes with prior ocular surgery history exhibited an inferior GATT success rate, likely attributed to scarring, in ammation, or brotic changes within the TM after previous trabeculectomy (5 eyes) or intraocular environmental disturbance caused by other ocular surgery (one eye with lens subluxation) [20,[22][23][24].…”
Section: Discussionmentioning
confidence: 94%
“…Lee et al. demonstrated that subvisible exposures (250–350 mW power) in PSLT resulted in thinning of the uveal meshwork and denudation of trabecular endothelial cells in cat eyes. Compared to ALT‐treated eyes, there was substantially less thermal damage and trabecular beams were not disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike ALT, the IOP‐lowering effect of PSLT was achieved without visible damage to TM (Lee et al. ). Like SLT, it provides uniform coverage of TM, but with some notable differences in the treatment parameters.…”
Section: Introductionmentioning
confidence: 99%
“…2 ) uses short pulse durations (10 to 20 ms) and predetermined patterns of spots, which results in reduction of thermal diffusion and surrounding tissue damage. In a recent experimental study, PLT resulted in less thermal damage than ALT, but did not effectively prevent late scarring of the trabecular meshwork [ 37 ]. A pilot study found a 24% reduction in IOP, without IOP spikes or inflammation, over 6 months of follow-up [ 38 ].…”
Section: Laser Trabeculoplastymentioning
confidence: 99%